The effect on infection of irradiated Fasciola gigantica (liver flukes) on goats (Capra hircus Linn) blood values - Tuasikal, Boky Jeanne; ., Suhardono (Indonesian Journal of Animal and Veterinary Sciences, 2006)
This experiment was carried out to study the effect of infection Fasciola gigantica irradiated by using 60Co to goatâs blood values. Twenty local male goats, ten to twelve old months, 15-20 kg of body weight were used for this study. The animals were divided into 5 groups consisting of four replications. Three groups received irradiated metacercariae of Fasciola gigantica using 45, 55 and 65 Gy respectively. One group was the positive control (goats were infected by non-irradiated metacercariae) and another one was the negative control (goats were not infected by metacercariae). Each goat received 350 metacercariae. Body weight, Eosinofil, PCV and Hb were measured every weeks for 20 weeks. The result indicated that pathogenicity of irradiated Fasciola gigantica was reduced. In all parameters, amongÂ  negative control group and three irradiation-groups showed non significant (P>0.05). Key Words: Fasciola gigantica, Irradiated, Eosinofil, Packed Cell Volume, Haemoglobin